QISQARTMA SO‘ZLARNING O‘ZBEK TILSHUNOSLIGIDA O‘RGANILISHI - Salomova G.А. (SCIENCE and SOCIETY, 2023)
The article addresses discussions about the role of the terminology "abbreviation" in Uzbek linguistics in the theory of Word formation and the history of the origin of the term "abbreviation". In this case, scientific research work of linguists dedicated to the problem was studied and scientific relations were given. It is also justified that" abbreviation " is not just an approach to language learning from the point of view of systemcentrism, but the presence of opportunities for an in-depth analysis of language units from the point of view of anthropocentrism. Therefore, the study necessitated focusing all its attention on anthropocentrism, that is, on a person who is the creator of personality, word and language in general.